OP66 Effect of pedometer-based walking interventions on long-term health outcomes: prospective 4-year follow-up of 2 randomised controlled trials using routine primary care data. (3rd September 2019) - Cook, DG; Harris, T; Limb, E; Hosking, F; Carey, IM; DeWilde, S; Furness, C; Wahlick, C; Ahmad, S; Kerry, S
Abstract : Background: Data are lacking from physical activity (PA) trials with long-term follow-up of both objectively measured PA levels and robust health outcomes. Two primary care 12-week pedometer-based walking interventions in adults and older adults (PACE-UP and PACE-Lift) found sustained objectively measured PA increases at 3 and 4 years, respectively. Using routine primary care data, we aimed to evaluate intervention effects on long-term health outcomes relevant to walking interventions. Methods: We downloaded primary care data for trial participants who gave written informed consent, for 4-year periods after their randomisation from the 7 PACE-UP and 3 PACE-Lift English general practices. The following new events were counted masked to intervention status for all participants, including those with pre-existing diseases (apart from diabetes, where existing cases were excluded): non-fatal cardiovascular; total cardiovascular (including fatal); incident diabetes; depression; fractures; and falls. Intervention effects on time to first event post-randomisation were modelled using Cox regression for all outcomes, except for falls, which used Poisson regression to allow for multiple events, adjusting for age, sex, and study. Absolute risk reductions (ARRs) and numbers needed to treat (NNT) were estimated. Results: Data were downloaded for 1297 (98%) of 1321 trial participants. Event rates were low (<20 per group) for outcomes, apart from fractures and falls. Cox Hazard ratios for time-to-first event after randomisation for interventions versus controls were: non-fatal cardiovascular 0·24 (95% CI 0·07 to 0·77); total cardiovascular 0.35 (0.12 to 0.91); diabetes 0·75 (0·42 to 1·36); depression 0·98 (0·46 to 2·07); and fractures 0·56 (0·35 to 0·90). Poisson incident rate ratio for falls was 1.09 (95% CI 0·83–1·43). ARR and NNT (95% CI) for cardiovascular events were: non-fatal 1.7% (0.5% to 2.1%), NNT=59 (48 to 194); total 1.6% (0.2% to 2.2%), NNT=61 (46 to 472); and for fractures 3.6% (0.8% to 5.4%), NNT 28 (19 to 125). Discussion: New cardiovascular events and fractures were significantly decreased in the intervention group at 4 years. Though no significant differences between intervention and control groups were demonstrated for other events, direction of effect for diabetes was protective. Short-term primary care pedometer-based walking interventions can produce long-term health benefits and should be more widely used to help address the public health inactivity challenge. Funding: Supported by the National Institute for Health Research (NIHR)